Penerapan Unsur Permufakatan Jahat Dalam Pasal 132 Ayat (1) Undang-Undang Republik Indonesia Nomor 35 Tentang Narkotika : Studi Putusan Pengadilan Negeri Medan Nomor : 2644/Pid.Sus/2017/Pn.Mdn - Gerry Anderson Gultom; Syafruddin Kalo; Muhammad Hamdan; Edi Yunara (Universitas Sumatera Utara, 2019)
Abstract. The application of evil consensus elements in Article 132 paragraph (1) of the Republic of Indonesia Law Number 35 of 2009 concerning Narcotics based on the decision of the Medan District Court Number: 2644 / Pid.Sus / 2017 / PN.Mdn on behalf of defendant Roni Sihombing and defendant Novrizal Batubara not in accordance with the full sound of Article 132 paragraph (1) of the Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics, this can be seen clearly from the indictment, proof of elements by the public prosecutor in the judicial panel's decision and elemental verdict in the decision that omits the phrase